CHILD SAFETY PRACTICES OF A GROUP OF IRAQI PATIENTS (Iraqi Journal of Medical Sciences, 2004)
Background: Accidents are the cause of death and disability for millions of children every year. Objectives: To study safety practices in a group of Iraqi parents, and its association with some demographic factors. Methods: A total of 360 parents of children aged 1-6 years were interviewed using a questionnaire form designed by the authors. Results: Majority (80%) of families keep medications in unsafe places, in addition to that 52.3%, 6.2% and 76.6% of parents keep antiseptics, kerosene and match boxes in unsafe places respectively. There was a significant association between keeping antiseptics in safe places with educational level of both parents and type of home (p